New plasma display panel packaging technology using electrostatic bonding method - Lee, DJ; Jeong, JW; Kim, YC; Lee, YH; Ju, BK; Cho, TS; Choi, EH; Jang, J (A V S AMER INST PHYSICS, 2001)
In this work, we have developed a plasma display panel (PDP) packaging technology, replacing the tip off tube with an indirect glass-to-glass electrostatic bond with intermediate layers of indium tin oxide and amorphous silicon. The glass-to-glass bonding for the packaging was performed at a low temperature of 180 degreesC while applying a bias of 250V(dc) in an environment of three mixed gases: He-Ne(27%)-Xe(3%). The 3.6 in. color alternating cur-rent-PDP with 8 mm thickness was successfully fabricated, with full white color brightness at a firing voltage of 190 V. Additionally, the luminance during the sustained period was 900-1000 cd/m(2). To investigate the capability of applying the glass bonding technology, the hermetic sealing test of the packaged panel was examined by a spinning rotor gauge for time variation. The leak rate test was performed with a helium detector. Since there is very low leakage through the bonded interface during 160 h, we can propose that it is highly possible to apply this technology to any vacuum packaged device. (C) 2001 American Vacuum Society.